Understanding and Addressing Truancy in Primary Schools of Awka South Local Government Area, Anambra State, Nigeria - Ann Ngozi Ugobueze; Sudiansyah; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2024)
In Awka South Local Government Area, truancy among primary school pupils is a significant issue that affects academic performance and overall student development, necessitating targeted interventions to improve attendance and support for students. The study employed a descriptive survey design to identify causes of truancy among primary school pupils in Awka South Local Government Area, Anambra State. It involved a population of 557 staff members, with a sample of 250 teachers from 15 schools selected randomly. Data was collected using a validated questionnaire with a four-point Likert scale and analyzed using descriptive statistics like frequency tables and mean scores. The mean score threshold for significance was set at 2.5. The method ensured accurate results by employing face and content validity checks and a test-retest reliability procedure. Findings indicate that truancy is recognized as unauthorized absence from school, influenced by factors such as lack of parental encouragement, excessive freedom, inadequate educational facilities, and peer influence. The study highlights significant effects, including increased risk of criminal behavior, academic struggles, and overall negative impact on the educational experience. To address these issues, the study recommends strategies such as incorporating hands-on activities, maintaining high academic expectations, creating a supportive classroom environment, and early identification of struggling students. This study contributes to a deeper understanding of truancy and dropout issues and offers practical solutions for improving student attendance and academic performance in the context of Awka South Local Government Area.